Reactive Oxygen Species: From Tumorigenesis to Therapeutic Strategies in Cancer - Iqra Attique (21493444) (2025)
Background Reactive oxygen species (ROS), a class of highly reactive molecules, are closely linked to the pathogenesis of various cancers. While ROS primarily originate from normal cellular processes, external stimuli can also contribute to their production. Cancer cells typically exhibit elevated ROS levels due to disrupted redox homeostasis, characterized by an imbalance between antioxidant and oxidant species. ROS play a dual role in cancer biology: at moderate levels, they facilitate tumor progression by regulating oncogenes and tumor suppressor genes, inducing mutations, promoting proliferation, extracellular matrix remodeling, invasion, immune modulation, and angiogenesis. However, excessive ROS levels can cause cellular damage and initiate apoptosis, necroptosis, or ferroptosis. Methods This review explores molecular targets involved in redox homeostasis dysregulation and examines the impact of ROS on the tumor microenvironment (TME). Literature from recent in vitro and in vivo studies was analyzed to assess how ROS modulation contributes to cancer development and therapy. Results Findings indicate that ROS influence cancer progression through various pathways and cellular mechanisms. Targeting ROS synthesis or enhancing ROS accumulation in tumor cells has shown promising anticancer effects. These therapeutic strategies exhibit significant potential to impair tumor growth while also interacting with elements of the TME. Conclusion The ROS serve as both promoters and suppressors of cancer depending on their intracellular concentration. Their complex role offers valuable opportunities for targeted cancer therapies. While challenges remain in precisely modulating ROS for therapeutic benefit, they hold promise as synergistic agents alongside conventional treatments, opening new avenues in cancer management. Other Information Published in: Cancer Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/cam4.70947